Ecological consequences as a result of non-rational use of mineral resources in the Republic of Kazakhstan - Teczke, J.; Shugaipova, Zh. (KSU Publ., 2018)
The article deals with the problems of inefficient use of natural resources during their extraction. The demand for minerals is steadily growing, the demand for them is determined primarily by demographic growth. Currently active development of minerals in Kazakhstan is under way. At the same time, there is a threat of their depletion, and pollution of the environment during the extraction of minerals can lead to irreversible consequences. The article raises the issue of the need to create as many enterprises as possible processing waste. The main problem with this is the absence of a state waste management system, which includes monitoring, storage, processing, recycling of industrial and domestic waste. Contamination of continental and oceanic waters by hydrocarbons is currently one of the main types of pollution of the hydrosphere by a modern civilized society. Sea and river currents, movements of air masses spread harmful pollution over long distances. Thus, the problem of environmental protection from the local, regional becomes a national or international. Kazakhstan, being a full-fledged member of the UN, should use international cooperation as a key to effective implementation of state environmental policy.
Қазақстан Республикасында минералды-шикізат ресурстардың тиімсіз пайдаланудың нəтижесінде пайда болатын экологиялық салдар
Экологические последствия в результате нерационального использования минерально-сырьевых ресурсов в Республике Казахстан
Keywords: extraction of minerals; pollution; environment; waste; protection of natural resources